2011
DOI: 10.1016/j.cell.2011.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Deficiency Promotes Genomic Instability in Early Stages of Cancer Development

Abstract: SUMMARY Chromosomal instability in early cancer stages is caused by stress on DNA replication. The molecular basis for replication perturbation in this context is currently unknown. We studied the replication dynamics in cells in which a regulator of S phase entry and cell proliferation, the Rb-E2F pathway, is aberrantly activated. Aberrant activation of this pathway by HPV-16 E6/E7 or cyclin E oncogenes significantly decreased the cellular nucleotide levels in the newly transformed cells. Exogenously supplied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
719
8
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 726 publications
(783 citation statements)
references
References 47 publications
35
719
8
6
Order By: Relevance
“…Overexpression of oncogenes such as HPV-16 E6/E7 and cyclin E has been demonstrated to lead to abnormal RB-E2F pathway which resulted in insufficient nucleotide pools during DNA replication and finally caused DNA damage and genome instability (Bester et al, 2011). Since the thymidine treatment in current step of this study also caused nucleotide pool unbalance hTERT-NHU cells (Fig.…”
Section: Future Workmentioning
confidence: 74%
See 1 more Smart Citation
“…Overexpression of oncogenes such as HPV-16 E6/E7 and cyclin E has been demonstrated to lead to abnormal RB-E2F pathway which resulted in insufficient nucleotide pools during DNA replication and finally caused DNA damage and genome instability (Bester et al, 2011). Since the thymidine treatment in current step of this study also caused nucleotide pool unbalance hTERT-NHU cells (Fig.…”
Section: Future Workmentioning
confidence: 74%
“…Replication stress or DNA damage is increased during o ncogenic transformation, which makes them more dependent upon DNA damage response pathways for cell survival (Bartkova et al, 2006;Bester et al, 2011;Vafa et al, 2002) . To cope with this stress many tumour cell lines elevate (Verlinden et al, 2007).…”
Section: -H2axmentioning
confidence: 99%
“…In this context, we believe that oncogenes that promote DNA replication, such as E2F or Myc, will upregulate factors that are necessary to cope with the increased replication rates (RS-buffers) as part of their transcriptional response. For instance, and in addition to the control of Chk1 by Myc and E2F, Myc also promotes the expression of RRM2, which would buffer RS by increasing dNTP pools [19]. Along these lines, we have recently showed that Chk1 expression is also under the control of the oncogene c-fos, which might facilitate transformation by limiting fos-induced RS [79].…”
Section: Rs As a Brake For Tumorigenesismentioning
confidence: 96%
“…The mutation of MCM4 or MCM2 reduces the activity of the MCM complex, limiting the amount of available back-up origins, which results in increased RS, genomic instability and a cancer-prone phenotype [14][15][16]. In contrast, the overexpression of certain oncogenes (Myc, Ras…) has the opposite effect and increases the firing of origins of replication, leading to a depletion of the cellular pool of nucleotides (dNTPs) [17][18][19][20][21]. The reduced level of dNTPs slows down the progression of the forks and increases the chance of fork stalling per se.…”
Section: Sources Of Replication Stress During Transformationmentioning
confidence: 99%
“…Des travaux antérieurs avaient révélé l'importance du stock intracellulaire de nucléotides libres dans la spécification des origines de réplication [6]. En outre, on savait que l'instabilité génomique due à l'expression d'oncogènes résultait, au moins en partie, d'un défaut de coordination entre la biosynthèse des nucléotides et la prolifération cellulaire [7]. D'où l'hypothèse que l'ajout de nucléosides au milieu de culture de cellules n'exprimant plus un de ces trois suppresseurs de CIN devait réduire l'instabilité chromosomique.…”
Section: Quels Sont Ces Suppresseurs De Cin ?unclassified